1985
DOI: 10.1002/jez.1402330302
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐phyletic bioactivity of arthropod neurohormones and molluscan ganglion extracts: Evidence of an extended peptide family

Abstract: Two structurally related arthropod neuropeptides, red pigment concentrating hormone (RPCH) and adipokinetic hormone (AKH), are potent excitors of the heart of the clam Mercenaria mercenaria. The response is bimodal: whereas the threshold for affected hearts is 1-3 X 10(-9) M, about 40% of the preparations are virtually unresponsive. Aqueous extracts of Mercenaria ganglia contain a substance which concentrates the red pigment in the erythrophores of intact destalked Uca pugilator and even of its isolated legs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The adipokinetic hormones are known to increase lipid mobilization in insect muscle during flight (Stone, Mordue, Batley & Morris, 1976), enhance hyperglycaemic activity and effect cardioacceleration in insects (Baumann & Gersch, 1982;Scarborough et al 1984) and increase myoactivity in insect skeletal muscle (O'Shea, Witten & Schaffer, 1984). An RPCH/AKH-like peptide with cardioexcitatory activity has also been isolated from the clam Mercenaria mercenaria (Greenberg et al 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The adipokinetic hormones are known to increase lipid mobilization in insect muscle during flight (Stone, Mordue, Batley & Morris, 1976), enhance hyperglycaemic activity and effect cardioacceleration in insects (Baumann & Gersch, 1982;Scarborough et al 1984) and increase myoactivity in insect skeletal muscle (O'Shea, Witten & Schaffer, 1984). An RPCH/AKH-like peptide with cardioexcitatory activity has also been isolated from the clam Mercenaria mercenaria (Greenberg et al 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Also, FMRFamide was found to stimulate release of red, but not black, pigment-concentrating hormone from isolated eyestalk tissues of Uca pugilator (Butler and Fingerman, 1985). Greenberg et al (1985) reported that FMRFamide, when injected into eyestalkless Uca pugilator, had no effect on the red pigment of this crab.…”
Section: Introductionmentioning
confidence: 92%
“…The AKH/RPCH and PDH/PDF peptides are clearly members of peptide families common to crustaceans and insects, serving different functions in each group. Substances related to these peptide families may also occur in mollusks (Greenberg et al, 1985;Elekes and Nässel, 1999), and PDH-ir cells have also been found in the pituitary of dogfish (Vallarino et al, 1991). In addition to the available probes (e.g., antibodies to characterized peptides), knowledge of the receptors for AKH/RPCH and PDH/PDF peptides would facilitate further studies on the distribution, evolution, and functions of these molecules.…”
Section: Perspectivesmentioning
confidence: 99%